Reform Processes within the IMF in the Context of Financial Crises: The Perspective of Analytical Eclecticism - Dragičević, Ognjen (International Problems, 2026)
This paper aims to provide a theoretical framework to address the constraints imposed by the epistemological exclusivity of researchers, manifested in the reliance on a singular theoretical approach or a limited array of interrelated theoretical concepts in the examination of the International Monetary Fund (IMF) development. The proposed framework offers an answer to the research topic addressing the function of analytical eclecticism in providing a more thorough and accurate elaboration of reform processes inside the IMF. The principal-agent (PA) approach, the theory of bureaucratisation, and the theory of crisis exploitation may all be unified relative to the theoretical framework built on this pragmatic epistemological stance. In keeping with the aforementioned, the article outlines the functions, pertinent ideas, application strategies, and connections between different theoretical perspectives in order to provide a unified and uniform starting point for the investigation of changes inside the IMF. The suggested theoretical framework acquires more coherence and strengthens its explanatory power by incorporating the idea of the axis of concretisation and connecting points. The perception of financial crises, such as the Asian financial crisis of 1997 and the financial crises of the late first decade of the twenty-first century, as both catalysts for the initiation and implementation of institutional reforms as well as a testing ground in which these changes are realised, represents a significant component in shaping this theoretical apparatus for researching reform processes within the Fund.